Creating interventions to transition long-lasting insecticide net distribution in Ghana - Philip Adongo; Phyllis Dako-Gyeke; Nana Yaw Peprah; Emmanuel Asampong; Philip Teg-Nefaah Tabong; Franklin Glozah; Adanna Nwameme; Ruby Hornuvo; Margaret Chandi (BMJ Open)
Objective Mass long-lasting insecticide net (LLIN) distribution campaigns are rolled out, as a part of the Ghana Malaria Strategic plan (2021–2025) which seeks to protect at least 80% of the population at risk with effective malaria prevention interventions. Although the mass LLIN distribution campaign indicates a comprehensive stakeholder engagement approach, it does not systematically transition into the basic primary healthcare structures within the Ghana Health Services. This paper presents the process and outcome of creating an innovative social intervention, which focuses on community mobilisation and capacity building of community health officers.Methods This study employed a concurrent triangulation mixed methods approach conducted across six districts in Eastern and Volta regions, Ghana. Findings were synthesised, grouped and further distilled to guide the participatory cocreation workshops. Cocreation involved participatory learning in action technique which is a practical, adaptive research strategy which enabled diverse groups and individuals to learn, work and act together in a cooperative manner.Results The results suggest the establishment of a Community Health Advocacy Team (CHAT). This would be necessary in efforts aimed at transitioning LLIN distribution campaign in communities. The role of the CHAT would be centred on key elements of community/social mobilisation and capacity building, all nested in a social and behaviour change communication strategies.Conclusion The research team is in the process of assessing the acceptability and feasibility of the CHAT intervention with all stakeholders in the various communities. Assessment of the effectiveness of the CHAT intervention would be done at a later time.